Time-Correlated Raman and Fluorescence Spectroscopy Based on a Silicon Photomultiplier and Time-Correlated Single Photon Counting Technique. Issue 2 (February 2013) - Zhang, Chunling; Zhang, Liying; Yang, Ru; Liang, Kun; Han, Dejun
We report a time-correlated Raman spectroscopy technique based on a silicon photomultiplier (SiPM) and a time-correlated single photon counting (TCSPC) technique to exploit the natural temporal separation between Raman and fluorescence phenomena to alleviate the high fluorescence background with conventional Raman detection. The TCSPC technique employed can greatly reduce the effect of high dark count rate (DCR) and crosstalk of SiPM that seriously hinder its application in low light level detection. The operating principle and performance of the 400 ps time resolution system are discussed along with the improvement of the peak-to-background ratio (PBR) for bulk trinitrotoluene (TNT) Raman spectrum relative to a commercial Raman spectrometer with charge coupled device (CCD). The fluorescence lifetime for solid TNT and Surface Enhanced Raman Scattering (SERS) spectrum for 10 −6 mol/L trace TNT have also been obtained by this system, showing excellent versatility and convenience in spectroscopy measurement.